On fuzzy po-Î“-semigroups - Kehayopulu, Niovi (Armenian Journal of Mathematics, 2015)
The results on fuzzy ordered semigroups (or on fuzzy semigroups) can be transferred to fuzzy ordered gamma (or to fuzzy gamma) semigroups. We show the way we pass from fuzzy ordered semigroups to fuzzy ordered gamma semigroups.